PENGARUH METODE LATIHAN SIRKUIT, METODE KONVENSIONAL TERHADAP KETERAMPILAN DASAR BOLA BASKET - Feby Elra Perdima (Journal Physical Education, Health and Recreation, 2017)
Based on the researchers abservation on the field, the student’s of SMA Negeri 1 Lebong Utara shill have lack of basic skill of basketball. This research aimed to explain the different effect between sirkuit exercise method and convensional method toward the increasing of student basic skill of basketball of SMA Negeri 1 Lebong Utara. This research is quasi experimental research the population of this research was 32 student. The sampling techique that used in this research was jenuh smpling techique. So that 32 student’s was choosen. the test used in this research were driible zig-zag, passing, under basket. Which aimed to know the student’s basic skill of basketball at SMA Negeri 1 Lebong Utara. Analysis technique that was used in this recearch was t-test. The result of data analysis showed that (1) sirkuit exercise method can increase the student basic skill of basketball at SMA Negeri 1 SMA Negeri 1 Lebong Utara (tobserved 16,77 > ttable α=0,051,75) (2) convensional method can increase the student’s basic skill of basketball at SMA Negeri 1 Lebong Utara (tobserved 9,25> ttable α=0,05 1,75) (3)  there is significant differences betwenn sirkuit exercise method with convensional method toward student’s basic skill of basketball at SMA Negeri 1 Lebong Utara (tobserved  3,50 > ttableα=0,051,75).